Antimicrobial susceptibility profile of human pathogenic bacteria isolated from raw milk - Reginara Teixeira da Silva; Joyce Bitencourt Athayde Lopes; Kleydejany Lima Lemos de Oliveira; José Carlos Ribeiro Júnior; Vanerli Beloti (Revista do Instituto de Latícinios Cândido Tostes, 2020)
The presence of bacteria in raw milk associated with the possible indiscriminate use of antimicrobials in dairy cattle can influence the emergence of resistant bacteria. The antimicrobial susceptibility profile of nine pathogenic bacterial strains isolated from raw milk from the State of Maranhão (Acinetobacter septicus, Hafnia alvei, Lactococcus garvieae, Staphylococcus epidermidis, Pantoea spp. and Klebsiella spp.) was evaluated in this study employing the test of disc diffusion antibiogram in Müller Hinton Agar, and for the interpretation of the sensitivity categories, it was used the criteria previously established. The least efficient antimicrobial was lincomycin, in which 83.33% of the strains showed resistance. Gentamicin and tetracycline were 100% efficient against the isolates of this study. Klebsiella spp. were resistant to more than 50% of the antimicrobials tested. However, multi-resistance was observed in 50% of the isolates: Hafnia alvei, Pantoea spp. and Klebsiella spp. The verified results demonstrate the multiresistance of pathogens of great importance for public health, and the raw milk as a possible source of delivery of these multi-resistant microorganisms.